The Relationship between Happiness and Mental Health among Saudi Women - Noura Abdulla Almadani; Mai B. Alwesmi (Brain Sciences, 2023)
The happiness and mental health of individuals are crucial for national developments. In Saudi Arabia, wellbeing occupies a central position in Vision 2030, along with women’s empowerment. Rapidly changing rights and responsibilities might result in more sources of stress. The aim of this study was to explore happiness and mental health among Saudi women during their contributions to a fast-growing nation in all fields. We assessed happiness and mental health (somatic symptoms, depression, anxiety, insomnia, and social dysfunction) in 308 Saudi women aged 15–50 years using a self-administered online survey comprising the short Oxford Happiness Questionnaire (OHQ-8) and the General Health Questionnaire (GHQ-28). The participants demonstrated general satisfaction yet showed rising psychological distress. Married women reported better mental health compared to single women, particularly with regards to anxiety, insomnia, and depression. Depression was highest among younger women. Employed women demonstrated lower social functioning compared to unemployed women. Women with a higher educational level showed lower social functioning. Happiness scores were significantly and inversely related with overall mental health scores as well as mental health subscales (somatic, anxiety, and depression), except for social dysfunction, which showed a positive correlation to happiness scores. This study contributes to the body of literature on women’s mental health and happiness by providing recommendations for improving both as well as directions for future research.